Pengaruh Budaya Organisasional dan Beban Kerja dengan Kepuasan Kerja sebagai Variabel Mediasi terhadap Kinerja Pegawai Negeri Sipil (PNS) Fungsional - Abdurrahman; Arief Subyantoro; Ambar Puji Harjanto (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The purpose of this study is to investigate how organizational culture and workload affect the performance of functional Civil Servants (PNS) at the Regional People's Representative Council (DPRD) Secretariat of the Special Region of Yogyakarta (DIY), with job satisfaction acting as a mediator between the two. This research uses a quantitative approach through a survey, where data is collected by distributing questionnaires to functional PNS at the DPRD Secretariat of DIY. The results of this study show that organizational culture has a significant positive effect on employee performance, with a ß value of 0.229 and a P-value of 0.004. In contrast, workload has a negative impact on employee performance, with a ß value of -0.252 and a P-value of 0.001. Job satisfaction is proven to play a mediating role in the relationship between organizational culture and employee performance, with a ß value of 0.268 and a P-value of 0.000. Additionally, job satisfaction also mediates the negative relationship between workload and employee performance, with a ß value of -0.186 and a P-value of 0.001. These findings indicate that a supportive organizational culture and effective workload management can encourage improved employee performance, while job satisfaction strengthens the positive impact of both factors. This study emphasizes the importance of creating a supportive work culture, efficient workload management, and efforts to enhance job satisfaction in order to achieve optimal employee performance.